COMPARING A WAY TO CALCULATE THE HEAT LOSS COEFFICIENT OF SOLAR FLAT PLATE COLLECTOR - suharta, herliyani; M. Sayigh, A.; Nasser, S.H. (185P -3466)
The need for a simple solution to derive the total heat loss coefficient, UL , is unquestioned as this reduces time to compute the performance of investigated system, especially in atmosphere when practicality is highly needed. This paper describes a simulation and comparison of several ways to obtained UL  The assumptions used and the method are described briefly. The analysis of the result shows that the derived equation (10) applied for solar box cooker type HS is the simplest. The long field test has proved its simplicity and people can understand it easily in practice. This numerical experiment is provided for the readers to validate this simple equation as it can be a tool for the scientist who needs to transfer their knowledge to a wider education level in the context to popularize the application of renewable energy.